The Influence of Brand Image and Brand Trust on Customer Satisfaction through Purchase Decisions as Intervening Variables in Fried Chicken Sabana in Malang City - Fahruddin Angga Pradana; Dwiyani Sudaryanti; Nur Hidayati (Budapest International Research and Critics University, 2022)
This study aims analyse the impact of Brand image, and Brand Trust on Customer Satisfaction through Purchase Decisions as Intervening Variables in Fried Chicken Sabana in Malang City. This survey is a quantitative survey using an explanatory survey method using a sample of 75 respondents, and uses a non-stochastic sampling method using a snowball sampling method. The data source used in this survey uses the primary data source in the method of data collection using surveys. The analytical method used Partial Least Square (PLS) method and software SmartPLS version 3.9 to analyse the hypothesis test. The conclusions of this study are as follows: (1) Brand Image has a positive but not significant effect on purchasing decisions at Sabana Fried Chicken in the city of Malang. (2) Brand Trust has a positive and significant effect on purchasing decisions at Sabana Fried Chicken in the city of Malang. (3) Brand Image has a positive and significant effect on customer satisfaction at Sabana Fried Chicken in the city of Malang. (4) Brand Trust has a positive and significant effect on customer satisfaction at Sabana Fried Chicken in the city of Malang. (5) Purchase decisions have a positive and significant impact on customer satisfaction at Sabana Fried Chicken in the city of Malang. (6) Brand Image has a positive but not significant effect on customer satisfaction through purchasing decisions as an intervening variable at Sabana Fried Chicken in the city of Malang. And (7) Brand Trust has a positive and significant effect on customer satisfaction through purchasing decisions as an intervening variable at Sabana Fried Chicken in the city of Malang.